DIABETES MELLITUS DENGAN HIPERTENSI MENINGKATKAN RISIKO CHRONIC KIDNEY DISEASE: STUDI KASUS KONTROL DI RS PANTI NIRMALA MALANG - Rea Ariyanti; Cecilia Wdijati Imam (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2020)
Chronic Kidney Disease (CKD) is a global public health problem with the prevalence and incidence of increased renal failure. Approximately 1 in 10 global populations suffers from chronic renal failure at a particular stage. There are several risk factors that are suspected to increase the incidence of Chronic Kidney Disease, one of which is Diabetes Mellitus. This study aims to determine the relationship between diabetes mellitus and chronic kidney disease in the Panti Nirmala Hospital. Research design is case-control. The sample amounted to 286 respondents, consisting of 143 case groups and 143 control groups. Data analysis using logistic regression analysis. The results of multivariable analyses showed that there are two confounding variables in the relationship of diabetes mellitus with CKD i.e. gender and age. In addition, diabetes mellitus also interacts with hypertension. Diabetes mellitus interacts with hypertension to increase the risk of CKD (OR=15.9; 95% CI 4.4 to 57.4; p=<0.001). After controlled by gender and age, Hypertension or a history of Hypertension, respondents with Diabetes Mellitus were 15.9 times more likely to have Chronic Kidney Disease than non-Diabetes Mellitus respondents.